Effects of Plyometric Training Method and Motor Ability on Lower-Limb Power in Junior High School Futsal Players: A 2×2 Factorial Study - Rindi Pista Dewa; Siti Ayu Risma Putri; Putri Cicilia Kristina (International Journal of Learning Reformation in Elementary Education, 2026)
Lower-limb power is essential for futsal because players repeatedly sprint, accelerate, decelerate, change direction, and jump, yet school-based extracurricular programs need training that is both effective and feasible for students with different readiness levels. This study examined whether the plyometric training method (squat jump vs. lunge-based plyometrics) and motor ability level (high vs. low) were associated with changes in lower-limb power in a junior high school futsal extracurricular program. Using a quasi-experimental 2×2 factorial framework, 40 students from SMP YPS Prabumulih City, Indonesia, completed a supervised plyometric program delivered over 16 sessions (four sessions per week) from October to November 2025. Motor ability testing classified students into high and low groups, and lower-limb power was assessed using a vertical jump test before and after training. Vertical jump scores increased significantly in all groups (p < 0.001): squat jump–low motor ability from 40.4 (SD 3.31) to 51.8 (SD 3.19), lunges–low from 37.0 (SD 3.30) to 47.9 (SD 2.60), squat jump–high from 36.9 (SD 4.04) to 48.2 (SD 4.37), and lunges–high from 44.2 (SD 2.53) to 54.8 (SD 2.20). These findings provide practical, school-context evidence that both plyometric options can be implemented and are linked with meaningful improvements across motor ability levels; however, conclusions about comparative superiority and interaction effects are limited by the single-site design and absence of a non-training control group. Future multi-site controlled studies with explicit factorial testing are recommended to confirm effectiveness and clarify method-by-motor-ability interactions.